Water-retaining and anti-cracking agent for cement stabilized macadam road base and preparation method of water-retaining and anti-cracking agent

By developing a water-retaining and crack-resistant agent for cement-stabilizing gravel road base, the problems of difficulty in maintaining and poor crack resistance of cement-stabilizing gravel base are solved, and the strength development and service life of the base layer are achieved.

CN119661114APending Publication Date: 2025-03-21TAIYUAN NAT & PROVINCIAL ROAD FENHE RESERVOIR SECTION CONSTR MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411892723.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Cement-stabilized gravel base has problems such as difficulty in maintenance and poor crack resistance during construction and use, resulting in insufficient strength development and early damage.

Method used

A water-retaining and cracking agent for cement-stabilizing the base layer of gravel roads was developed, and an admixture with water-retaining and cracking resistance was prepared by synthesizing raw materials such as acrylic acid, ammonium persulfate, sodium hydroxymethylsulfate, ethylene diacrylate, azobisisobutyronitrile, sodium carbonate, magnesium oxide, diatomaceous earth and calcium sulfaluminate.

Benefits of technology

The water-retaining and cracking agent can absorb and slowly release moisture in the cement-stabilized gravel base layer, reduce maintenance conditions, and extend the service life of the base layer by improving the structural strength and crack resistance of the base layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201019890000151
    Figure BDA0005201019890000151
  • Figure BDA0005201019890000161
    Figure BDA0005201019890000161
  • Figure BDA0005201019890000162
    Figure BDA0005201019890000162
Patent Text Reader

Abstract

The invention discloses a water-retention anti-cracking agent for a cement stabilized macadam road base and a preparation method thereof, and belongs to the technical field of road base additives. The adhesive is prepared from the following raw materials in percentage by weight: 32%-35% of acrylic acid, 5%-7% of ammonium persulfate, 6%-8% of hydroxymethyl sodium sulfite, 6%-8% of ethylene glycol diacrylate, 0.3%-0.5% of azodiisobutyronitrile, 6%-8% of sodium carbonate, 8%-13% of magnesium oxide, 10%-15% of diatomite and 10%-14% of calcium sulphoaluminate. The water-retention anti-cracking agent can be used as a road base additive to improve the strength of a cement-stabilized base and effectively reduce the cracking problem caused by self-shrinkage of the cement-stabilized base.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road base admixtures, and particularly relates to a water-retaining and anti-cracking agent for a cement-stabilized crushed stone road base and a preparation method thereof. Background Art

[0002] With the rapid development of the highway network, it covers most parts of the country and greatly improves the convenience of transportation. Cement-stabilized crushed stone is widely used as a good road base material in the base construction process. In the use environment of the road base, cement-stabilized crushed stone has significant advantages. It has high compressive strength and durability, and can withstand the test of traffic loads and harsh environments for a long time. Its good water resistance makes the base remain stable in a humid environment and is not easily eroded by water. It has good freeze-thaw resistance and is suitable for various climatic conditions. This material not only provides a sufficient strength foundation, but also has a relatively simple and fast construction process, which can improve construction efficiency and reduce costs. It has economic benefits and is an important road base material. However, in practical applications, this material still has some problems that need to be solved and optimized.

[0003] A large part of the strength of cement-stabilized gravel base comes from the connection between the hydration products produced by cement hydration and the aggregate. Therefore, certain curing conditions are required. The temperature and humidity during curing have an impact on its strength. However, this material is relatively dense after hardening, which makes it difficult for water to penetrate smoothly into the base layer, affecting its curing effect and subsequent strength development. Therefore, it is necessary to solve the water demand problem during the long-term hydration of cement and reduce the curing conditions. Secondly, crack resistance is another major challenge facing cement-stabilized gravel. Although the material has high compressive strength, its tensile strength is relatively weak, and it is easy to crack under the influence of temperature changes, traffic loads, etc. At the same time, cement materials are prone to shrinkage cracks. Once these cracks are formed, they will accelerate the invasion of harmful substances and lead to early damage to the base layer.

[0004] There are some solutions to the problems of difficult maintenance and poor crack resistance of cement-stabilized crushed stone base. For example, by improving the mixture ratio and construction process, the density and strength of the base can be improved. Advanced non-destructive detection technologies, such as seismic wave detection and ultrasonic detection, can be used to detect cracks and damage in the base in a timely manner, so as to carry out targeted maintenance. However, these methods do not specifically solve the maintenance problems and poor crack resistance of cement-stabilized crushed stone base.

[0005] Therefore, based on the above situation, a modifier is developed to reduce the maintenance conditions during the construction of cement-stabilized base layers, improve the strength of cement-stabilized base layers, and effectively reduce the cracking problem caused by their own shrinkage. This can not only reduce the project cost, but also reduce the maintenance and repair costs, and has broad development prospects. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a water-retaining and anti-cracking agent for cement-stabilized gravel road base and a preparation method. The water-retaining and anti-cracking agent as a road base admixture can improve the strength of cement-stabilized base and effectively reduce the cracking problem caused by its self-shrinkage.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The invention provides a water-retaining and anti-cracking agent for a cement-stabilized macadam road base. The water-retaining and anti-cracking agent is prepared from the following raw materials by weight: 32% to 35% of acrylic acid, 5% to 7% of ammonium persulfate, 6% to 8% of sodium hydroxymethylsulfoxylate, 6% to 8% of ethylene glycol diacrylate, 0.3% to 0.5% of azobisisobutyronitrile, 6% to 8% of sodium carbonate, 8% to 13% of magnesium oxide, 10% to 15% of diatomaceous earth and 10% to 14% of calcium sulfoaluminate.

[0009] In one embodiment, the present invention is made of the following raw materials, by weight: 34% acrylic acid, 6% ammonium persulfate, 7% sodium hydroxymethylsulfoxylate, 8% ethylene glycol diacrylate, 0.5% azobisisobutyronitrile, 7.5% sodium carbonate, 12% magnesium oxide, 13% diatomaceous earth, and 12% calcium sulfoaluminate.

[0010] In one embodiment, acrylic acid is a colorless transparent liquid, wherein the acrylic acid content is ≥99.5% by mass and the water content is ≤0.1% by mass;

[0011] Sodium hydroxymethyl sulfoxylate is a white solid powder, wherein the content of sodium hydroxymethyl sulfoxylate is ≥99% by mass fraction.

[0012] In one embodiment, the ammonium persulfate is a colorless or white crystalline powder, wherein the ammonium persulfate content is ≥ 98.5% by mass, the water content is ≤ 0.1%, and the pH value of a 5% aqueous solution is ≤ 5.3.

[0013] In one embodiment, the sodium carbonate is a white crystalline powder, wherein the sodium carbonate content is ≥ 98.0% by mass and the water-insoluble matter is ≤ 0.10% by mass.

[0014] In one embodiment, the magnesium oxide is white fine crystals, wherein the magnesium oxide content is ≥93.0%, the calcium oxide content is ≤1.5%, and the hydrochloric acid insoluble matter is ≤0.20%, by mass fraction.

[0015] In one embodiment, the diatomaceous earth is an off-white or light yellow powder, wherein, by mass fraction, the water-soluble matter is ≤0.3%, the acid-soluble matter is ≤0.30%, and the pH value is 5.5-7.5.

[0016] In one embodiment, the calcium sulfoaluminate is a white or light yellow crystalline powder, wherein the calcium sulfoaluminate content is ≥ 99% by mass and the pH value is 8-10.

[0017] The present invention also provides a method for preparing a water-retaining and anti-cracking agent for a cement-stabilized macadam road base, comprising the following steps:

[0018] Acrylic acid and ammonium persulfate are mixed in water to prepare a solution, and then sodium hydroxymethylsulfoxylate is added to obtain a homogeneous aqueous solution A;

[0019] The initiator azobisisobutyronitrile is added to the aqueous solution A and continuously stirred to cause a polymerization reaction. Calcium sulphoaluminate is added under continuous stirring. After the stirring is completed, the solution is allowed to stand to obtain a hydrogel B.

[0020] Sodium carbonate is used to prepare aqueous solution C with deionized water, and aqueous solution C is added into hydrogel B to form colloid D, and colloid D is dried and crushed to obtain colloid particles E;

[0021] Ethylene glycol diacrylate is prepared into a saturated solution with deionized water, which is evenly sprayed on the surface of the rubber particles E, followed by drying and heating; magnesium oxide and diatomaceous earth powder are then evenly sprinkled on the surface of the rubber particles E, which are then heated; and screening is performed to obtain a water-retaining and anti-cracking agent for cement-stabilized macadam road base.

[0022] In one embodiment, the mass concentration of the solution is 20% to 30%; the mass fraction of the aqueous solution C is 30%.

[0023] In one embodiment, the particle size of the water-retaining and anti-cracking agent for cement-stabilized macadam road base is 100 to 300 μm.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention provides a water-retaining and anti-cracking agent for cement-stabilized macadam road base. First, the synthesized material is used in the base, can absorb water and expand during the mixing process of the cement-stabilized macadam base, evenly spread in the mixture, and closely connected with cement and aggregate. After the base construction is completed, as the free water in the system is continuously reduced due to reaction or evaporation, the water stored in the material is slowly released, effectively filling the gap required for cement hydration, reducing the maintenance conditions of cement-stabilized macadam, so that it can also have good strength development when used in high temperature and arid areas, greatly broadening its use conditions. At the same time, it has a small particle size and a large specific surface area, can better contact with the cement-stabilized macadam base, and play a role in water retention and water release.

[0026] Secondly, the synthesized water-retaining and anti-cracking agent contains diatomaceous earth, which is an insoluble inorganic powder with stable chemical properties, low expansion coefficient, and good acid and alkali resistance. It can improve the structural strength of the admixture in the base structure and play a certain skeleton support role. The free water in the base often leaves gaps after reaction or natural loss, induces cracks, and reduces the strength of the base. The admixture prepared by the present invention can still have considerable structural strength after releasing water, and the volume will not be significantly reduced. Compared with the general cement-stabilized crushed stone base, after adding the present invention, its shrinkage strain is greatly reduced, and the generation of cracks caused by water loss is reduced.

[0027] Finally, magnesium oxide and calcium sulfoaluminate are added to the water-retaining and anti-cracking agent synthesized by the present invention for the cement environment. Magnesium oxide is not only used as part of the surface-changing cross-linking agent in the preparation process, but can react to generate flaky magnesium hydroxide crystals after being added to the base layer, and calcium sulfoaluminate can react to generate calcium sulfoaluminate. These two substances are intertwined with the hydrated calcium silicate generated by cement hydration. After adding these two substances, the admixture is more tightly combined with the base layer. After the introduction of the admixture, it will not separate from the interface of the original cement-stabilized crushed stone, resulting in a decrease in strength. On the contrary, both magnesium hydroxide crystals and calcium sulfoaluminate have certain expansibility, so that the admixture can more effectively resist the shrinkage of cement-stabilized crushed stone, thereby inhibiting the generation of cracks and achieving an anti-cracking effect.

[0028] The preparation process of the present invention is relatively simple, and when used, it only needs to be mixed with cement-stabilized crushed stone materials in proportion, and does not require the operation guidance of professional technicians. It can conveniently improve the strength and crack resistance of the cement-stabilized crushed stone base, effectively ensure the engineering quality of the road base, reduce the later maintenance costs, and increase the service life. It has important value in expanding the application scenarios of the cement-stabilized crushed stone base and extending the service life of the cement-stabilized crushed stone base. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0030] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0031] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0032] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0033] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0034] The present invention provides a water-retaining and anti-cracking agent for cement-stabilized macadam road base and a preparation method thereof. The water-retaining and anti-cracking agent effectively ensures the strength development of the cement-stabilized macadam base through the water absorption and water-retaining properties of a high-performance water-absorbing resin, reduces the maintenance conditions during the construction process, and the water-retaining capacity of the high-performance water-absorbing resin enables the base to have sufficient water to supply cement for hydration reaction when it is constructed in high-temperature and arid areas. The added calcium sulfoaluminate can react with the calcium hydroxide produced by cement hydration, improve the bonding performance of the admixture with the base, and also effectively reduce the cracking problem caused by its self-shrinkage, reduce the expansion of reflected cracks inside the base, and improve the life of the base.

[0035] In general, this additive can improve the strength and crack resistance of cement-stabilized crushed stone base, effectively ensure the engineering quality of the road base, reduce the later maintenance costs, and increase the service life. It is of great value in expanding the application scenarios of cement-stabilized crushed stone base and extending the service life of cement-stabilized crushed stone base.

[0036] The above-mentioned water-retaining and anti-cracking agent for cement-stabilized macadam road base modification is made of the following raw materials: acrylic acid, ammonium persulfate, sodium hydroxymethylsulfoxylate, 1,4-butanediol, ethylene glycol diacrylate, azobisisobutyronitrile, sodium carbonate, magnesium oxide, diatomaceous earth, calcium sulfoaluminate, and calcium phosphate.

[0037] Specifically, a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification is made of the following raw materials, measured by weight: 32% to 35% acrylic acid, 5% to 7% ammonium persulfate, 6% to 8% sodium hydroxymethylsulfoxylate, 6% to 8% ethylene glycol diacrylate, 0.3% to 0.5% azobisisobutyronitrile, 6% to 8% sodium carbonate, 8% to 13% magnesium oxide, 10% to 15% diatomaceous earth, and 10% to 14% calcium sulfoaluminate.

[0038] Preferably, the invention is made of the following raw materials by weight: 34% acrylic acid, 6% ammonium persulfate, 7% sodium hydroxymethylsulfoxylate, 8% ethylene glycol diacrylate, 0.5% azobisisobutyronitrile, 7.5% sodium carbonate, 12% magnesium oxide, 13% diatomaceous earth and 12% calcium sulfoaluminate.

[0039] A method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, the method adopts the formula of the water-retaining and anti-cracking agent for cement-stabilized macadam road base modification as described above, and the method specifically comprises the following steps:

[0040] Step 1, weigh the above raw materials according to mass;

[0041] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 20% to 30%, stir magnetically for 5 minutes, add sodium hydroxymethylsulfoxylate, and stir magnetically for another 10 minutes to obtain a homogeneous aqueous solution A;

[0042] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0043] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0044] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0045] Step six, sieving with a vibrating screen machine to control the particle size of the final product between 100 and 300 μm to obtain the desired high-performance admixture.

[0046] In one embodiment, the specification requirements of each raw material are as follows:

[0047] Acrylic acid is a colorless crystal or transparent liquid with a pungent odor. It is miscible with water, ethanol, and ether, and easily polymerizes in the air. Acrylic acid is a colorless transparent liquid, in which the acrylic acid content is ≥99.5% by mass and the water content is ≤0.1%.

[0048] Ammonium persulfate is a colorless or white crystalline powder with a chemical formula of (NH4)2S2O8 and a molecular weight of 228.201. It is highly oxidizing and corrosive. Ammonium persulfate is a colorless or white crystalline powder with a mass fraction of ≥98.5% ammonium persulfate content, ≤0.1% water content, and a pH value of ≤5.3 for a 5% aqueous solution.

[0049] Sodium hydroxymethyl sulfoxylate is a white solid powder with a pungent odor and is easily soluble in water. Sodium hydroxymethyl sulfoxylate is a white solid powder, in which the content of sodium hydroxymethyl sulfoxylate is ≥99% by mass.

[0050] Ethylene glycol diacrylate is a light yellow, transparent, slightly viscous liquid with a molecular weight of 170.16. It is relatively stable at room temperature and is not easy to decompose.

[0051] Azobisisobutyronitrile is a white needle-shaped crystal, soluble in organic solvents such as methanol, ethanol, acetone, ether, and petroleum ether.

[0052] Sodium carbonate is a white powder. It is soluble in water and glycerol, but insoluble in ethanol. Its aqueous solution is strongly alkaline, with a pH value of 11.6. Sodium carbonate is a white crystalline powder, in which the sodium carbonate content is ≥98.0% by mass and the water-insoluble matter is ≤0.10%.

[0053] Magnesium oxide is white fine crystals, almost insoluble in water, soluble in dilute acid. It easily absorbs moisture and carbon dioxide in the air. Magnesium oxide is white light powder, of which, by mass fraction, magnesium oxide content ≥ 93.0%, calcium oxide ≤ 1.5%, and hydrochloric acid insoluble matter ≤ 0.20%.

[0054] Diatomaceous earth is off-white or light yellow powder, with a hardness of 1 to 1.5, but the diatom skeleton is 4.5-5. The melting point is 1400 to 1650°C, and the general density is 1.9 to 2.35 g / cm 3 It has high liquid adsorption capacity, large surface area, low conductivity to sound, heat and electricity, is easily soluble in alkali, and insoluble in any acid except hydrofluoric acid. It provides a skeleton structure for the curing agent.

[0055] Diatomaceous earth is off-white or light yellow powder, of which, by mass fraction, water-soluble matter is ≤0.3%, acid-soluble matter is ≤0.30%, and pH value is 5.5-7.5.

[0056] Calcium sulphoaluminate is a white or light yellow crystalline powder, which improves the compatibility of the curing agent with the cement base, and has a certain expansion property to reduce the problem of cement cracking. Calcium sulphoaluminate is a white or light yellow crystalline powder, in which the calcium sulphoaluminate content is ≥99% by mass and the pH value is 8-10.

[0057] The cement is ordinary Portland cement with a strength grade of 42.5.

[0058] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0059] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0060] Example 1

[0061] This example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0062] Acrylic acid is 34%, ammonium persulfate is 6%, sodium hydroxymethylsulfoxylate is 7%, ethylene glycol diacrylate is 8%, azobisisobutyronitrile is 0.5%, sodium carbonate is 7.5%, magnesium oxide is 12%, diatomaceous earth is 13%, and calcium sulfoaluminate is 12%.

[0063] Step 1, weigh the above raw materials according to mass;

[0064] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 25%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0065] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0066] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0067] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0068] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0069] Example 2

[0070] This example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0071] Acrylic acid is 32%, ammonium persulfate is 7%, sodium hydroxymethylsulfoxylate is 8%, ethylene glycol diacrylate is 8%, azobisisobutyronitrile is 0.5%, sodium carbonate is 7.5%, magnesium oxide is 13%, diatomaceous earth is 10%, and calcium sulfoaluminate is 14%.

[0072] Step 1, weigh the above raw materials according to mass;

[0073] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 20%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0074] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0075] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0076] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0077] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0078] Example 3

[0079] This example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0080] Acrylic acid is 32%, ammonium persulfate is 5%, sodium hydroxymethylsulfoxylate is 8%, ethylene glycol diacrylate is 8%, azobisisobutyronitrile is 0.5%, sodium carbonate is 7.5%, magnesium oxide is 12%, diatomaceous earth is 15%, and calcium sulfoaluminate is 12%.

[0081] Step 1, weigh the above raw materials according to mass;

[0082] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 25%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0083] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0084] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0085] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0086] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0087] Example 4

[0088] This example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0089] Acrylic acid is 34%, ammonium persulfate is 6%, sodium hydroxymethylsulfoxylate is 6%, ethylene glycol diacrylate is 7%, azobisisobutyronitrile is 0.3%, sodium carbonate is 6%, magnesium oxide is 12%, diatomaceous earth is 14.7%, and calcium sulfoaluminate is 14%.

[0090] Step 1, weigh the above raw materials according to mass;

[0091] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 25%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0092] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0093] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0094] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0095] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0096] Example 5

[0097] This example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0098] Acrylic acid is 35%, ammonium persulfate is 7%, sodium hydroxymethylsulfoxylate is 7%, ethylene glycol diacrylate is 8%, azobisisobutyronitrile is 0.5%, sodium carbonate is 7.5%, magnesium oxide is 13%, diatomaceous earth is 12%, and calcium sulfoaluminate is 10%.

[0099] Step 1, weigh the above raw materials according to mass;

[0100] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 30%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0101] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0102] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0103] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0104] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0105] Example 6

[0106] This example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0107] Acrylic acid is 35%, ammonium persulfate is 7%, sodium hydroxymethylsulfoxylate is 8%, ethylene glycol diacrylate is 6%, azobisisobutyronitrile is 0.5%, sodium carbonate is 8%, magnesium oxide is 8%, diatomaceous earth is 14%, and calcium sulfoaluminate is 13.5%.

[0108] Step 1, weigh the above raw materials according to mass;

[0109] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 24%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0110] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0111] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0112] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0113] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0114] Comparative Example 1

[0115] This comparative example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0116] Acrylic acid is 32%, ammonium persulfate is 9%, sodium hydroxymethylsulfoxylate is 10%, ethylene glycol diacrylate is 15%, azobisisobutyronitrile is 1.5%, sodium carbonate is 7.5%, magnesium oxide is 10%, and diatomaceous earth is 15%.

[0117] Step 1, weigh the above raw materials according to mass;

[0118] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 25%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0119] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, and then standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0120] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0121] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide and diatomaceous earth powder on the surface of the colloid E, and continue heating for 0.5 h;

[0122] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0123] Comparative Example 2

[0124] This comparative example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0125] Acrylic acid is 34%, ammonium persulfate is 6%, sodium hydroxymethylsulfoxylate is 7%, ethylene glycol diacrylate is 10%, azobisisobutyronitrile is 0.5%, sodium carbonate is 9.5%, diatomaceous earth is 18%, and calcium sulfoaluminate is 15%.

[0126] Step 1, weigh the above raw materials according to mass;

[0127] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 22%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0128] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0129] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0130] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle diatomaceous earth powder on the surface of the colloid E and continue heating for 0.5 h;

[0131] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0132] Comparative Example 3

[0133] This example provides a method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base modification, which is composed of the following raw materials by mass fraction:

[0134] Acrylic acid is 32%, ammonium persulfate is 8%, sodium hydroxymethylsulfoxylate is 9%, ethylene glycol diacrylate is 10%, azobisisobutyronitrile is 0.5%, sodium carbonate is 8.5%, magnesium oxide is 16%, and calcium sulfoaluminate is 16%.

[0135] Step 1, weigh the above raw materials according to mass;

[0136] Step 2: Mix acrylic acid and ammonium persulfate in water to prepare a solution with a mass concentration of 25%, stir magnetically for 5 minutes, add sodium hydroxymethyl sulfoxylate, and stir magnetically for 10 minutes to obtain a homogeneous aqueous solution A;

[0137] Step 3, adding an initiator azobisisobutyronitrile to aqueous solution A and stirring continuously to cause a polymerization reaction, stirring the reaction solution for 25 minutes, adding calcium sulfoaluminate while stirring continuously, and standing for 1 to 2 hours after the stirring to wait for the reaction to end, thereby obtaining hydrogel B;

[0138] Step 4: prepare sodium carbonate into a 30% aqueous solution C with deionized water, add the aqueous solution C into the hydrogel B, stir the reaction solution for 10 minutes to form a colloid D, and dry and crush the colloid D to obtain colloid particles E;

[0139] Step 5: prepare ethylene glycol diacrylate into a saturated solution with deionized water, spray it evenly on the surface of the colloid E, and then put it into an oven and heat it at 100° C. to 120° C. for 0.5 h; then evenly sprinkle magnesium oxide powder on the surface of the colloid E and continue heating for 0.5 h;

[0140] Step 6: Screening with a vibrating screen machine to control the particle size of the final product to be between 100 and 300 μm to obtain the desired high-performance admixture.

[0141] Performance Testing

[0142] When testing fluidity, add the prepared admixture to the cement paste of uniform proportion to test its fluidity. At the same time, add a blank control group. When testing the unconfined compressive strength and shrinkage rate, add the prepared admixture and cement stabilized gravel to the mixing equipment for mixing. Standard curing for 28 days, test its unconfined compressive strength, shrinkage rate, and calculate the shrinkage rate ratio of 28 days. The admixture dosage is 0.2% of the cement mass. The specific performance indicators are shown in the following table.

[0143] Table 1 Cement paste fluidity test results

[0144]

[0145]

[0146] Table 2 28d cement stabilized crushed stone compressive strength and reduction rate test results

[0147]

[0148] It can be seen from the examples in Table 1 that adding a water-retaining and anti-cracking agent to cement can significantly reduce the fluidity of cement paste. The addition of admixtures absorbs a large amount of free water, thereby reducing the fluidity of cement paste. The data of the six example groups show that the different composition ratios of raw materials will lead to certain differences in the water absorption performance of the prepared admixtures, but they still have considerable water absorption capacity. The comparative example reduces the content of acrylic acid and increases the ratio of initiator and crosslinking agent, and its effect on the fluidity of cement paste is greatly reduced, indicating that acrylic acid is very important for the water absorption characteristics. With the gradual reduction of acrylic acid, the effect of admixtures on the fluidity of cement paste is getting smaller and smaller.

[0149] As can be seen from Table 2, the addition of admixtures can effectively improve the 28d compressive strength of cement stabilized crushed stone, but it can be found that the acrylic acid content does not significantly promote the development of strength, because in the laboratory environment, the humidity of standard curing is very suitable for cement hydration development, and the water retention effect of the admixture is not significant, but the added sulphoaluminate has a certain early strength effect. Therefore, it can be found that with the increase of the content of diatomaceous earth, sulphoaluminate and other substances, the 28d unconfined compressive strength of the sample is significantly improved. Similarly, as the product of sulphoaluminate and magnesium oxide, calcium sulfonate and magnesium hydroxide have an expansion effect. Therefore, with the increase of the ratio of these two raw materials, the shrinkage rate of the base layer has a significant decrease, reflecting the resistance effect of the admixture to the self-shrinkage of the base layer.

[0150] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A water-retaining and anti-cracking agent for cement-stabilized macadam road base, characterized in that: The invention is made of the following raw materials by weight: 32% to 35% acrylic acid, 5% to 7% ammonium persulfate, 6% to 8% sodium hydroxymethylsulfoxylate, 6% to 8% ethylene glycol diacrylate, 0.3% to 0.5% azobisisobutyronitrile, 6% to 8% sodium carbonate, 8% to 13% magnesium oxide, 10% to 15% diatomaceous earth and 10% to 14% calcium sulfoaluminate.

2. The water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 1, characterized in that: The invention is made of the following raw materials by weight: 34% acrylic acid, 6% ammonium persulfate, 7% sodium hydroxymethylsulfoxylate, 8% ethylene glycol diacrylate, 0.5% azobisisobutyronitrile, 7.5% sodium carbonate, 12% magnesium oxide, 13% diatomaceous earth and 12% calcium sulfoaluminate.

3. The water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 1, characterized in that: Acrylic acid is a colorless transparent liquid, in which the acrylic acid content is ≥99.5% by mass and the water content is ≤0.1%; Sodium hydroxymethyl sulfoxylate is a white solid powder, wherein the content of sodium hydroxymethyl sulfoxylate is ≥99% by mass fraction.

4. The water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 1, characterized in that: Ammonium persulfate is a colorless or white crystalline powder, wherein, by mass fraction, the ammonium persulfate content is ≥ 98.5%, the water content is ≤ 0.1%, and the pH value of a 5% aqueous solution is ≤ 5.

3.

5. The water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 1, characterized in that: Sodium carbonate is a white crystalline powder, wherein the sodium carbonate content is ≥ 98.0% by mass and the water-insoluble matter is ≤ 0.10%.

6. The water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 1, characterized in that: Magnesium oxide is white fine crystals, wherein by mass fraction, the magnesium oxide content is ≥93.0%, the calcium oxide content is ≤1.5%, and the hydrochloric acid insoluble matter is ≤0.20%.

7. The water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 1, characterized in that: Diatomaceous earth is off-white or light yellow powder, of which, by mass fraction, water-soluble matter is ≤0.3%, acid-soluble matter is ≤0.30%, and pH value is 5.5-7.

5.

8. The water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 1, characterized in that: Calcium sulphoaluminate is a white or light yellow crystalline powder, wherein the content of calcium sulphoaluminate is ≥99% by mass and the pH value is 8-10.

9. A method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base according to any one of claims 1 to 8, characterized in that: The following steps are involved: Acrylic acid and ammonium persulfate are mixed in water to prepare a solution, and then sodium hydroxymethylsulfoxylate is added to obtain a homogeneous aqueous solution A; The initiator azobisisobutyronitrile is added to the aqueous solution A and continuously stirred to cause a polymerization reaction. Calcium sulphoaluminate is added under continuous stirring. After the stirring is completed, the solution is allowed to stand to obtain a hydrogel B. Sodium carbonate is used to prepare aqueous solution C with deionized water, and aqueous solution C is added into hydrogel B to form colloid D, and colloid D is dried and crushed to obtain colloid particles E; Ethylene glycol diacrylate is prepared into a saturated solution with deionized water, which is evenly sprayed on the surface of the rubber particles E, followed by drying and heating; magnesium oxide and diatomaceous earth powder are then evenly sprinkled on the surface of the rubber particles E, which are then heated; and screening is performed to obtain a water-retaining and anti-cracking agent for cement-stabilized macadam road base.

10. The method for preparing a water-retaining and anti-cracking agent for cement-stabilized macadam road base according to claim 9, characterized in that: The mass concentration of the solution is 20% to 30%; the mass fraction of the aqueous solution C is 30%; and the particle size of the water-retaining and anti-cracking agent for cement-stabilized macadam road base is 100 to 300 μm.